Produktivitas Usaha Mikro dan Kecil Industri Makanan di Indonesia - Syifa Fauziah; Amzul Rifin; Andriyono Kilat Adhi (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2020)
Micro and small enterprises (SMEs) has a contributes to economic growth. Labour contributions in SMEs even more than ninety percent of the total labour. While most of the SMEs is in the processing industry. The objectives of this research is to measure labour productivity and to know factors that affecting technical efficiency on SMEs in the food industry. Samples collected from the survey then were continued with cleaning data until 2250 unit of samples were taken. Technical efficiency and factors that affecting were described by quantitative analysis method Stochastic Frontier Analysis. Results showed that more than half of enterprises has a efficient. About seventeen percent of business that have below average in technical effficiency values. While small enterprises more technically efficient than micro enterprises. Level of education, working hours and working day, market alocation and variabel of percentage of own capital had a significant on technical efficiency.